Quantification of frequency-dependent genetic architectures in 25 UK Biobank traits reveals action of negative selection - Armin P. Schoech (Nature Portfolio, 2019)
Negative selection removes deleterious genetic variation, and can influence genetic architectures and evolution of complex traits. Here, the authors analyze data from 25 UK Biobank diseases and complex traits, and quantify frequency-dependent genetic architectures which suggests actions of negative selection.